Analysis of the Subsurface Structure Using the HVSR Method in Jorong Air Putih Lima Puluh Kota Regency - Afifah, Nurul (Journal of Experimental and Applied Physics, 2025)
This study aims to analyze the subsurface structure and soil stability in the Jorong Air Putih area, Lima Puluh Kota Regency, West Sumatra Province, using the Horizontal to Vertical Spectral Ratio (HVSR) method. This area is known as a landslide-prone zone influenced by steep topography, complex geological conditions, and relatively high seismic activity. Therefore, understanding subsurface characteristics is crucial for geological disaster mitigation efforts and sustainable infrastructure planning. Data collection was conducted through microtremor surveys at 18 measurement points distributed across the study area. The data were analyzed using Easy HVSR software to calculate important seismic parameters, including the dominant frequency value , amplification factor , , seismic vulnerability index (Kg), and estimated shear wave velocity (Vs). The analysis results show that the dominant frequency values range from 0.4 Hz to 10.6 Hz, reflecting variations in the thickness and properties of subsurface layers, ranging from soft sediments to hard rocks. The measured amplification factor ranges from 1.22 to 3.20, indicating the potential for seismic wave amplification in certain soil layers. The seismic vulnerability index is mostly low, but there is one observation point showing moderate vulnerability, The shear wave velocity value.